The Effectiveness of Sprint Training and Hollow Sprints in Improving Leg Muscle Power in Players of the Tumbak Raya Mitra Soccer Club - Achmad Paturusi; Saputra A.S Paturusi; Nofie Sondakh (International Journal of Social Service and Research, 2026)
The Effectiveness of Sprint Training and Hollow Sprint on Increasing Leg Muscle Power in Tumbak Raya Southeast Minahasa Football Club Players. This study aims to measure and analyze empirical data on the effectiveness of sprint training and hollow sprint on improving leg muscle power ability in Tumbak Raya Southeast Minahasa football club players. The method used is the "true experimental method". The research design refers to the experimental design using "One group pre-test and post-test design" and "randomized control groups group pre-test and post-test design". The population is the entire Tumbak Raya football club players. The sample was selectively sampled by 24 players based on the height and length of the legs were relatively the same. They were divided into 2 groups, namely the sprint training experimental group (n=12) and the hollow sprint experimental group (n=12). The instrument is a "standing board jump test". The data analysis technique used was an independent statistical test of one sample and two samples with a real level of a=0.05. The results of the study show; (1) There was an effect of sprint training on the improvement of leg muscle power in players of the Tumbak Raya Minahasa Southeast Minahasa football club, with the results of the observation t-test (tob) = 17,238 > ttab = 2,101. (2) There was an effect of hollow sprint training on the improvement of leg muscle power in players of the Tumbak Raya Southeast Minahasa football club, with the results of the observation t-test (tob) = 12,558 > ttab = 2.101, and (3) There was a difference in the effect between sprint training and hollow sprint trainingon the improvement of leg muscle power in Tumbak Raya Southeast Minahasa Football Club players, with the results of the tob test = 4,680 > ttab value = 2.074, the results of the average score of the two training models are more effective in increasing leg muscle power with sprint training.